Holocaust Education in Quebec: Teachers’ Positioning and Practices - Moisan, Sabrina; Hirsch, Sivane; Audet, Geneviève (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2015)
Teaching about the Holocaust is mandatory in many societies. This prescription is justified by authorities with many reasons: educating pupils for a better understanding of human rights, peace, war, genocide, critical thinking, historical thinking, racism, etc. The Holocaust can carry a very strong moral and emotional charge. But why do teachers choose to teach about it when it is not compulsory? And how do they do this? Which resources do they use? What content is their teaching based on? This case study focuses on three high school history teachers in Quebec and explores their educational objectives in teaching the Holocaust and related pedagogical practices, including a field trip to the Montreal Holocaust Memorial Centre.